Numerical Study of Unsteady Blood Flow in The Carotid Stenosis Model (Future Science, 2022)
A numerical study has been carried out to analyze the unsteady behavior of velocity distribution and wall shear stress in the stenotic artery using computational fluid dynamics. The 2D channel geometry was an idealized geometry model of the internal carotid artery and the stenosis is modeled as an asymmetric square step corresponding to a 25% reduction in the internal carotid artery reduction. The blood flow is considered a Newtonian fluid. The wall of the artery is considered rigid. A uniform flow is assumed in the inlet boundary condition and zero gradient pressure is considered as an outlet boundary condition setup. The recirculation region and low WSS are visible at the post-stenosis location (at x = 0h to x = 10h). Although the velocity profile recovers fully developed at x = 12h to the outlet, the lower WSS is still observed. This numerical result indicates that the presence of stenosis in the internal carotid artery will catalyze the formation of new plaques in the neighborhood area of the post-stenosis location